Family environments, school resources, and educational outcomes - Kao, Grace; Park, Hyunjoon (Bingley, U.K. : Emerald, 2016)
Contributions come from authors spread around the globe, illuminating how the efficacy and ideologies of schooling variably unfold in differing national and historical contexts. Written by sociologists, anthropologists, economists, and cultural critics, this journal offers lively and accessible empirical work to a broad audience.
How schools matter : the need for a contextual perspective / Douglas B. Downey -- Preschool enrollment, classroom instruction, elementary school context, and the reading achievement of children from low-income families / Robert Crosnoe, Aprile D. Benner, Pamela Davis-Kean -- The consequences of principal and teacher turnover for school social resources / Paul Hanselman ... [et al.] -- The effect of mothers' educational credentials on children's outcomes : does being a first-generation or continuing-generation college graduate matter? / Susan A. Dumais, Laura Nichols -- Children's highbrow cultural activities and academic achievement in Hong Kong / Soo-Yong Byun, Suet-ling Pong -- The hopes carry them on : early educational expectations and later educational outcomes in rural Gansu, China / Yuping Zhang.
Print version record
Keywords: Social Science -- Sociology -- General; Education; Home and school; Educational psychology